REGIONAL GOVERNMENT SPENDING EFFICIENCY ON HEALTH AND EDUCATION IN DECENTRALIZATION ERA : EVIDENCE FROM INDONESIA - Iskandar, Azwar; Saragih, Rahmaluddin (JURNAL INFO ARTHA, 2019)
The purpose of this paper is to assess spending efficiency of regional governments in Indonesia on health and education during the fiscal decentralization period year of 2010-2017. Relying on a sample of 33 provinces as regional government, this paper compute efficiency scores adopting nonparametric frontier that estimated by Data Envelopment Analysis (DEA) to study spending inefficiency. Results of the paper show that in west regions, Bali, Bangka Belitung, DI Yogyakarta, Jawa Tengah, and Kep. Riau relatively most efficient in public spending both on health and education in period of study. DKI Jakarta and Jawa Barat have efficient score on health, and Bengkulu has efficient score on education. On the other hand, in east regions, Gorontalo, Kalimantan Tengah, Kalimantan Timur and Sulawesi Utara were also most efficient in public spending on health and education services. Maluku and Sulawesi Tenggara have efficient score on health, and Kalimantan Selatan, Maluku Utara, Nusa Tenggara Barat, and Sulawesi Barat have efficient score on education. The results show that provinces in east regions of Indonesia were relatively more efficient in public spending both on health and education for promoting equal distribution of income